Modeling the Impact of Riparian Hollows on River Corridor Nitrogen Exports - Rogers, D. Brian; Newcomer, Michelle E.; Raberg, Jonathan H.; Dwivedi, Dipankar; Steefel, Carl; Bouskill, Nicholas; Nico, Peter; Faybishenko, Boris; Fox, Patricia; Conrad, Mark; Bill, Markus; Brodie, Eoin; et al. (Frontiers in Water, 2021)
Recent studies in snowmelt-dominated catchments have documented changes in nitrogen (N) retention over time, such as declines in watershed exports of N, though there is a limited understanding of the controlling processes driving these trends. Working in the mountainous headwater East River Colorado watershed, we explored the effects of riparian hollows as N-cycling hotspots and as important small-scale controls on observed watershed trends. Using a modeling-based approach informed by remote sensing and in situ observations, we simulated the N-retention capacity of riparian hollows with seasonal and yearly hydrobiogeochemical perturbations imposed as drivers. We then implemented a scaling approach to quantify the relative contribution of riparian hollows to the total river corridor N budget. We found that riparian hollows primarily serve as N sinks, with N-transformation rates significantly limited by periods of enhanced groundwater upwelling and promoted at the onset of rainfall events. Given these observed hydrologic controls, we expect that the nitrate (NO3-) sink capacity of riparian hollows will increase in magnitude with future climatic perturbations, specifically the shift to more frequent rainfall events and fewer snowmelt events, as projected for many mountainous headwater catchments. Our current estimates suggest that while riparian hollows provision approximately 5-20% of NO3- to the river network, they functionally act as inhibitors to upland NO3- reaching the stream. Our work linking transient hydrological conditions to numerical biogeochemical simulations is an important step in assessing N-retaining features relative to the watershed N budget and better understanding the role of small-scale features within watersheds.